A prophylactic fresh frozen plasma transfusion leads to a possible case of transfusion-related acute lung injury. (21st July 2014) - Banerjee, Debasree; Hussain, Rashid; Mazer, Jeffrey; Carino, Gerardo
Abstract : A 39-year-old man with cholangiocarcinoma presented with fever and abdominal pain. He was hypotensive, jaundiced and had right upper quadrant tenderness. Laboratory testing showed a leucocytosis, elevated liver function tests, total bilirubin and International Normalised Ratio (INR). Given the concern for cholangitis, the patient was given antibiotics and three units of fresh frozen plasma (FFP) before biliary drain placement. After drain placement, and within 3 h of receiving blood products, the patient became tachypnoeic and hypoxic with a chest X-ray revealing new bilateral airspace disease. The rapid development of respiratory distress was determined to most likely be transfusion-related acute lung injury (TRALI). He rapidly progressed to intubation and required 100% FiO2, high positive-end expiratory pressure (PEEP) and intermittent-prone ventilation for 48 h but eventually recovered and was extubated. TRALI is an under-recognised aetiology for respiratory distress in the critically ill. Adopting a conservative transfusion strategy may prevent TRALI.